Photography: a tool for historical records in Nigeria (2012)
History is either oral or written. Whichever of these forms it assumes, one thing is clear; it brings to memory records of past or present events, places or situations. The question of two or more people experiencing the same or somewhat similar graphic imagery of oral or written history becomes pertinent. This situation is improbable. However, with the aid of photographs, the graphic representation of an event is frozen in time and space, thereby making it possible for a number of people to view the record of a past event that they may not have witnessed. With video, we can even hear voices and experience life in such events. Using pictures from old newspapers, published books and from private collections, this essay attempts a pictorial social, cultural and political history of the country. It also appraised the development of photography in Nigeria. This essay avers that photography is a veritable tool for documenting historical records for posterity and an endeavour that should be encouraged and communalised